2015
DOI: 10.1128/jvi.00695-15
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Env and Nef Cooperatively Contribute to Plasmacytoid Dendritic Cell Activation via CD4-Dependent Mechanisms

Abstract: Plasmacytoid dendritic cells (pDCs) are the major source of type I IFN (IFN-I) in response to human immunodeficiency virus type 1 (HIV-1) infection. pDCs are rapidly activated during HIV-1 infection and are implicated in reducing the early viral load, as well as contributing to HIV-1-induced pathogenesis. However, most cell-free HIV-1 isolates are inefficient in activating human pDCs, and the mechanisms of HIV-1 recognition by pDCs and pDC activation are not clearly defined. In this study, we report that two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 79 publications
(129 reference statements)
1
13
0
Order By: Relevance
“…7 In association with HIV, the pDC produce IFN-a under the stimulation of HIV components. 14 The case presented here showed high levels of pDC infiltration in the upper dermis of the HIV-associated psoriatic plaques, which were resolved with antiretroviral therapy alone. These findings suggest that the condition of HIV infection may activate pDC and recruit them to the dermis, leading the immunological cascade of psoriasis.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…7 In association with HIV, the pDC produce IFN-a under the stimulation of HIV components. 14 The case presented here showed high levels of pDC infiltration in the upper dermis of the HIV-associated psoriatic plaques, which were resolved with antiretroviral therapy alone. These findings suggest that the condition of HIV infection may activate pDC and recruit them to the dermis, leading the immunological cascade of psoriasis.…”
Section: Discussionmentioning
confidence: 60%
“…The pDC are, therefore, considered to potentially play a role in the onset of psoriasis because pDC infiltrate into the skin and produce IFN‐α early in the course of disease . In association with HIV, the pDC produce IFN‐α under the stimulation of HIV components . The case presented here showed high levels of pDC infiltration in the upper dermis of the HIV‐associated psoriatic plaques, which were resolved with antiretroviral therapy alone.…”
Section: Discussionmentioning
confidence: 78%
“…While the spatiotemporal model of pDC sensing has been most clearly evaluated using synthetic TLR9 agonists (CpG), we have shown that the model also applies to HIV and TLR7, whereby HIV traffics to early endosomes in pDC, activating IRF7 signaling rather than NF-κB signaling [ 22 , 23 ]. The upstream events that determine activation of each of these pathways, and in particular, HIV virion trafficking in pDC, are currently unknown, however, prior studies suggest that HIV envelope may play a major role [ 13 , 30 , 31 ]. Here we demonstrate that HIV trafficking and pDC phenotype is predominantly determined by envelope-CD4 interaction, such that manipulation of HIV envelope or CD4 intracellular trafficking enables modulation of divergent sensing of HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Methods for the isolation of human PBMCs were described previously (55), and PBMCs were cryopreserved until use. CD4 T cells were negatively isolated from PBMCs by using an untouched Dynabeads human CD4 T cell kit (catalog number 11352D; Invitrogen) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%